Familial Pleuroparenchymal Fibroelastosis - Ozkaya, S.; Dirican, A.; Bekdemir, O. S.; Yuksel, C.; Gun, S.; Yildirim, F.; Zorlu, D. (Amer Thoracic Soc, 2018)
…
International Conference of the American-Thoracic-Society -- MAY 18-23, 2018 -- San Diego, CA